Cinema ticketing system / Ng Gah Chuan - Ng, Gah Chuan (2003)
Cinema Ticketing System (CTS) is my final year thesis project title. CTS is a web-enable management system. It designed for a local cinema organization use. With this capability, the system is able to provide tightly integrated online real-time reservation, payment transaction order and electronic information dissemination such as email and promotion to its members. Moviegoers, employee and the management level are the target group who will benefit if the system developed in a success. This report introduces the CTS project. It defines the objectives, significance, Scope and project schedule that should identified before development of this system. Beside that, it ha a description on the topic studied and researched during the literature research and literatur review. In the analysis phase, the V Model with prototyping approach was selected for the development process because the strengths of both the V model and prototyping can be combined in a single project and reduces the risk involved. The development tool chosen was Microsoft Visual Studio .NET whereas the web server was internet Information Server 5.0 with back end database Microsoft SQL Server 2000. All these will be deployed on Windows 2000 Advance Server platform. For the movement, Golden Screen Cinema is the only cinema company who implement an online booking service in Malaysia. But the service thus far has many weaknesses that could be exploited into a much reliable and efficient system both to the management and customer. From here, lies a great opportunity to change and improve a system that promises better service in the business service sector that implies E-Commerce.